Matrix Metalloproteinases in Myocardial Infarction and Heart Failure - DeLeon-Pennell, Kristine Y. (Prog Mol Biol Transl Sci, 2017)
Cardiovascular disease (CVD) is the leading cause of death, accounting for 600,000 deaths each year in the U.S. In addition, heart failure accounts for 37% of healthcare spending. Matrix metalloproteinases (MMPs) increase after myocardial infarction (MI) and correlate with left ventricular dysfunction in heart failure patients. MMPs regulate the remodeling process by facilitating extracellular matrix (ECM) turnover and inflammatory signaling. Due to the critical role MMPs play during cardiac remodeling, there is a need to better understand the pathophysiological mechanism of MMPs, including the biological function of the downstream products of MMP proteolysis. Future studies developing new therapeutic targets that inhibit specific MMP actions to limit the development of heart failure post-MI are warranted. This book chapter focuses on the role of MMPs post-MI, the efficiency of MMPs as biomarkers for MI or heart failure, and the future of MMPs and their cleavage products as targets for prevention of post-MI heart failure.